Ex 3.3
Ex 3.3, 2 Important
Ex 3.3, 3 Important
Ex 3.3, 4
Ex 3.3, 5 (i) Important
Ex 3.3, 5 (ii)
Ex 3.3, 6 Important
Ex 3.3, 7
Ex 3.3, 8 Important
Ex 3.3, 9 Important
Ex 3.3, 10 You are here
Ex 3.3, 11 Important
Ex 3.3, 12
Ex 3.3, 13 Important
Ex 3.3, 14
Ex 3.3, 15
Ex 3.3, 16 Important
Ex 3.3, 17
Ex 3.3, 18 Important
Ex 3.3, 19
Ex 3.3, 20
Ex 3.3, 21 Important
Ex 3.3, 22 Important
Ex 3.3, 23 Important
Ex 3.3, 24
Ex 3.3, 25
Last updated at April 16, 2024 by Teachoo
Ex 3.3, 10 Prove that sinβ‘(π + 1)π₯ sinβ‘(π + 2)π₯+cosβ‘(π + 1)π₯ cosβ‘(π + 2)π₯=cosβ‘π₯ Solving L.H.S. We know that cos ( A β B) = cos A cos B + sin A sin B Here, A = (n + 1)x ,B = (n + 2)x Hence sinβ‘(π+1)π₯ sinβ‘(π+2)π₯+cosβ‘(π + 1)π₯ cosβ‘(π + 2)π₯ = cos [ (n + 1)x β (n + 2)x ] = cos [ nx + x β nx β 2x ] = cos [ nx β nx + x β 2 x ] = cos (0 β x ) = cos (β x) = cos x = R.H.S. Hence , L.H.S. = R.H.S. Hence proved